(untitled) (Промышленный Транспорт Казахстан, 2025)
The paper addresses the problem of development of competitive electricity markets in relationships that were formed by the enactment of the law "On electric power industry", according to which it is prohibited to combine the activities of the transfer and sale and purchase of electricity. The author considers types of violations of antitrust laws in the retail and wholesale electricity market, and draws conclusions on the further development of competition in the electricity market. Since the state energy company (hereinafter RAO UES) has been established in 1992, there were active discussions about how to develop the Russian electric power industry. Various schemes of corporatization, privatization, consolidation with high-yielding types of industries (e.g., aluminum production), expansion of the production chain by including the production of equipment for the power industry were proposed as the main reform ideas. Most of these projects were rejected due to infringement of the interests of "RAO UES" private shareholders, or contradictions to the public interest.